Performance Evaluation of Floating Solar Power Plant in Sidobandung Bojonegoro - Rahmat, Mohammad Basuki; Poetro, Joessianto Eko; Setiyoko, Annas Singgih; Widodo, Hendro Agus; Asri, Purwidi; Hidayat, Edy Prasetya; Indartono, Arie; Budiawati, Ratna; Mudjanarko, Sri Wiwoho (LPPM of NAROTAMA UNIVERSITY, 2023)
Sidobandung Village is a village that will develop the potential as a tourism village. One of the potentials that has been successfully built is a reservoir. With the construction of the reservoir in this village, tourism activities began to be seen. The number of visitors who came increases the village's income. Yet, Currently it only open on daytime conditions. Therefore, in its development, there is a desire to open services at night. The problem is how to reduce electricity costs. One of the facilities to support this is to build a floating generator (PLTS) which was built in collaboration with one of the expert vocational colleges in the field of floating buildings located in Surabaya. This floating PLTS is a renewable energy source, in accordance with the village's wish to become an educational tourism village. This floating PLTS is expected to be able to supply 30 lamps which each having a power of 50 watts for street lighting around the reservoir. The total lamp load is about 100 watts. The PLTS system that was built consists of 10 solar cell panels, each solar cell panel has a capacity of 330 WP. With a total of 4 batteries with specifications of 12 Volt 200 Ah. This system is being evaluated. The evaluation results show that the battery capacity is only able to supply 15 lamps for 12 hours. So to supply all the required load, 12 batteries are needed.